Cultural assimilation: Learning and sorting - Stein Monteiro (Review of Economic Analysis (REA), 2021)
Immigrants have greater exposure to co-ethnics, leading to fewer incentives to learn the local culture and assimilate. In this paper, the exposure channel through which source country richness affects assimilating immigration is modelled through neighbourhood location choices and incentives to learn the local culture in the host country. Two equilibrium outcomes are identified, in which, there is either only assimilating immigration in at least one neighbourhood of the host country (sorting equilibrium) when immigration is from a rich source country, or there is some non-assimilating immigration in all neighbourhoods (mixed equilibrium) when immigration is from a poor source country. The presence of this exposure channel is tested using data from the Longitudinal Survey of Immigrants in Canada: waves 1-3. Learning, rather than sorting into co-ethnic communities, is the main factor operating in the exposure channel between source country richness and assimilating immigration.
Keywords: J15; Z13; 330; Cultural Assimilation; Language Proficiency; Pre-immigration Experience